Self-esteem and burnout syndrome among physicians of critical care units. A correlational study. Hospital Nacional Dos de Mayo. Lima–Peru - Contreras-Camarena , Carlos (2021)
Objective: To determine the role of self-esteem against burnout syndrome (BOS) among physicians of the Department of Emergency and Critical Care of the Hospital Nacional Dos de Mayo (HNDM). Lima–Peru, 2020. Materials and methods: An analytical and correlational study. Sixty-six (66) physicians were surveyed. The variables “selfesteem” and “burnout” were measured with the Rosenberg Self-Esteem Scale and the Maslach Burnout Inventory–Human Services Survey (MBI–HSS), respectively. The odds ratio was used to establish the probability of burnout according to the self-esteem level, and the Pearson correlation coefficient was used to determine the correlation of major variables. A value of p < 0.05 was considered as statistically significant. Results: Sixteen point six six percent (16.66 %) of the study population showed emotional fatigue; 28.78 %, depersonalization; and 25.75 %, low personal fulfillment. Females achieved lower levels of personal fulfillment and males, higher levels of depersonalization. Twenty-five point seven five percent (25.75 %) had low self-esteem and, in this group, the frequency of burnout was three to six times higher. A negative correlation was found between self-esteem and emotional tiredness (Pearson’s r: –0.551), and between self-esteem and depersonalization (Pearson’s r: –0.298). Conversely, a positive correlation was found between self-esteem and personal fulfillment (Pearson’s r: 0.499). Conclusions: One out of four physicians had low self-esteem. Burnout was more common in this group, compared to the medium–high self-esteem group. Seventy-one point two one percent (71.21 %) of the physicians had at least one compromised dimension, 19.70 % had two compromised dimensions and 13.64 % had an established BOS. Low self-esteem may favor burnout, while high self-esteem may play a protective role.